Training & prompting pre-service teachers’ noticing in a standardized classroom simulation – a mobile eye-tracking study - Telgmann, Leonie; Müller, Katharina (Frontiers in Education, 2023)
Numerous events happening in classrooms require a teacher to select important and filter out irrelevant information. This crucial and challenging skill is referred to as noticing. For noticing classroom management events pre-service teachers have a smaller knowledge base and little teaching experience compared to expert teachers. Supporting pre-service teachers in developing their classroom management knowledge and noticing skill is, thus, of great importance for teacher education. Previous research finds positive effects of interventions on teachers' noticing during video observation. To our knowledge, no studies depict noticing during teaching. We examined N = 46 preservice teachers' noticing with regard to classroom management during classroom teaching in a quasi-experimental between-subjects design. Pre-service teachers' took part in a standardized classroom simulation after a classroom management training, with one group receiving prompting regarding evidence-based classroom management strategies before and during the classroom simulation and one group receiving only training. We also included a control group without classroom management training. To assess differences in pre-service teachers' noticing, the classroom simulation elicited comparable conditions, including standardized classroom management events and student behaviour. Mobile eye-tracking as well as retrospective video observations were used to explore teachers' event-related and global noticing. Event-related noticing was assessed via count and accuracy of noticed classroom management events. Global noticing included objective parameters of teachers eye movements (visit/fixation counts and duration) onto the students in the standardized classroom simulation. The results show that training and prompting significantly affected pre-service teachers' event-related noticing, with both experimental groups making fewer target and time errors compared to the control group. No significant differences were found with regard to global noticing. This includes fixation and visit count and duration on students. Correlational analysis showed a positive association between higher noticing accuracy and share of fixations on students. This study expands upon previous empirical research using mobile eyetracking to obtain objective measures of teachers' noticing. It sheds light on the relevance of knowledge for teachers' noticing during teaching. It also takes a first step towards understanding how pre-service teachers' noticing during classroom teaching can be promoted through fostering knowledge about classroom management through a training.